Analisis Putusan Mahkamah Agung Nomor 50 P/HUM/2018 tentang Pembatalan Permenkumham Nomor 25 Tahun 2017 - Narasoma, Deno Ukida; Permadi, Iwan; Wardhani, Diah Aju Wisnu (Universitas Negeri Malang, 2020)
This study aimed to analyze the reasons the Supreme Court issued a Supreme Court Decision Number 50 P/HUM/2018 which decided the cancellation of the Minister of Law and Human Rights Regulation Number 25 of 2017 and analyze the legal consequences of the decision on new notary candidates. This study used normative juridical with a statutory approach and historical approach. The reasons the Supreme Court issued Supreme Court Decision Number 50 P/HUM/2018 were influenced by two factors, i.e., juridical and non-juridical factors. The legal consequences of the Supreme Court Decision Number 50 P/HUM/2018 for new notary candidates was the disappearance of the notary candidate’s obligation to take the notary appointment exam and the emergence of problems related to the clarity of the qualifications that should be completed to register as a notary because the ruling resulted in a legal vacuum related to the terms of the conditions in the appointment of a public notary.